The Problems in Implementing the Independent Learning Curriculum at the Motivator School of Sambaliung Elementary School - Herjayanti, Risna; Noryani, Noryani; Merliana, Merliana; Warman, Warman (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
The Merdeka Curriculum is an educational program for primary and secondary school students that focuses on instilling national ideals and encouraging pupils to think critically, creatively, independently, and socially intelligently. In order to successfully implement the Merdeka Curriculum, this study seeks to offer ideas and actions that can be implemented in that direction. The focus of this study is on SD Negeri 005 Sambaliung's (one of the Mover Schools) endeavors to determine the barriers to, and solutions to, implementing the Merdeka Curriculum, as well as the learning strategies put in place to achieve these goals. The principal, VP of curriculum, teachers, and students are the subjects of this descriptive qualitative study. To ensure that the data collected is reliable and comprehensive, this study relies on observation, interviews, and recording. Data analysis involved sorting, reducing, presenting, and drawing conclusions. The results of the study found that the obstacles faced by related educators include the preparation of teaching tools that are not optimal, limited internet networks and lack of infrastructure. However, concrete efforts continue to be made by the Principal and educators at SD Negeri 005 Sambaliung such as the implementation of coaching clinics for educators and education personnel, aligning local knowledge, and utilizing open spaces.